2017
DOI: 10.1002/ejp.1125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duloxetine on pain and walking distance in neuropathic pain models via modulation of the spinal monoamine system

Abstract: The findings of this study suggest that duloxetine may be an effective treatment of broad neuropathic pain states, including neuropathic low back pain. The analgesic effects of duloxetine might be mediated by alterations of the descending pain modulatory pathways in the spinal cord, independent of the antidepressant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
1
7
0
1
Order By: Relevance
“…25 Atf-3 mRNA in DRG neurons was found to increase after nerve damage. 26 This indicated that Atf3 may be a candidate genetic marker in the progression of NP. Additionally, chemokines, by binding to Gpr151, play important roles in pathological pain states activated by either peripheral nerve injury or inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…25 Atf-3 mRNA in DRG neurons was found to increase after nerve damage. 26 This indicated that Atf3 may be a candidate genetic marker in the progression of NP. Additionally, chemokines, by binding to Gpr151, play important roles in pathological pain states activated by either peripheral nerve injury or inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…to be due to activation of the descending inhibitory pain pathway, which leads to normalization of the dysfunctional process, a finding that is supported in rat neuropathic pain models 21,22) . The observed reduction in pain intensity might be partially explained by the duloxetineinduced analgesic effect, independent of its antidepressant and anxiolytic effects.…”
Section: Discussionmentioning
confidence: 75%
“…In an animal study, the analgesic effects of pregabalin were weaker in the cauda equina compression model without an improvement in the walking distance than in the partial sciatic nerve ligation model; the expression of α 2 δ-1 subunit significantly increased only in the partial sciatic nerve ligation model and remained unchanged in the cauda equina compression model. However, duloxetine had analgesic effects in both models and improved walking distance in the cauda equina compression model 40 . The expression of the α 2 δ-1 subunit may be specific to the injury type.…”
Section: Discussionmentioning
confidence: 89%